A New Paclitaxel Formulation Based on Secretome Isolated from Mesenchymal Stem Cells Shows a Significant Cytotoxic Effect on Osteosarcoma Cell Lines - Alessia Giovanna Santa Banche Niclot; Elena Marini; Ivana Ferrero; Francesco Barbero; Elena Rosso; Ivana Fenoglio; Alessandro Barge; Augusto Pessina; Valentina Coccè; Francesca Paino; Katia Mareschi; Franca Fagioli (MDPI AG, 2023)
Background: Osteosarcoma (OS) represents a rare cancer with an unfavorable prognosis that needs innovative treatment. The aim was to isolate a secretome from mesenchymal stem cells (MSCs) that are treated with paclitaxel (PTX)-containing microvesicles as a drug delivery system and analyze its cytotoxic effects on OS cell lines (SJSA, MG63, and HOS). Methods: Three batches of secretome (SECR-1, SECR-2, and SECR-3) were produced from three bone marrow (BM) MSCs samples treated for 24 h with 15 µg/mL of PTX or with a standard medium. The viability of the OS cell lines after 5 days of exposure to SECR-1-2-3 (pure and diluted to 1:2 and 1:4) was analyzed with an MTT assay. The same SECR batches were analyzed with high-performance liquid chromatography (HPLC) and with a nanoparticle tracking assay (NTA). Results: A statistically significant decrease in the viability of all OS cell lines was observed after treatment with SECR-PTX 1-2-3 in a dose-response manner. The NTA analyses showed the presence of nanoparticles (NPs) with a mean size comparable to that of extracellular vesicles (EVs). The HPLC analyses detected the presence of PTX in minimal doses in all SECR batches. Conclusions: This proof-of-concept study showed that the conditioned medium isolated from MSCs loaded with PTX had a strong cytotoxic effect on OS cell lines, due to the presence of EV and PTX.